The Influence of Work Environment and Work Motivation on Job Satisfaction and Implications for Employee Performance (Study on BPJS Employment Kanwil SUMBARRIAU) - Yuyulianda, Eko; Heri, Helwen; N, Arizal (Yayasan Education Al Aqsho Modern, 2023)
The phenomenon that occurred, BPJS Ketenagakerjaan in any challenge must be able to provide the best public services. Some of the problems above are strong reasons for conducting research, besides that they are also supported by the existence of research gaps in several interesting studies to review. The location of this research is at the BPJS Ketenagakerjaan Regional Office of West Sumatra with the address: Komplek Mega Asri Green Office A09-A12, Jl. Arifin Ahmad, Tengkerang Tengah, Kec. Marpoyan Damai, Pekanbaru City, Riau. After that make observations and interviews with research subjects. The subjects of this study were employees working at the BPJS Ketenagakerjaan in the West Sumatra Regional Office. As the population in this study were all employees at the BPJS Ketenagakerjaan Regional Office of West Sumatra, totaling 43 people. The number of samples in this study were 43 respondents and sampling were carried out using the sample quota method, namely taking the entire sample from the population. Based on the results of the analysis, several conclusions can be drawn: 1) the first to fifth research hypotheses prove that the work environment and work motivation affect employee performance. 2) work environment has a significant effect on employee performance through job satisfaction. Significant influence can be seen from the results of the Path Coefficient. This means that the work environment has a significant effect on performance through employee job satisfaction at the BPJS Ketenagakerjaan Regional Office of West Sumatra. 3) Then the seventh hypothesis mediation test predicts that work motivation has a significant effect on employee performance through job satisfaction at the BPJS Ketenagakerjaan Regional Office of West Sumatra Riau. This means that work motivation has a significant effect on performance through employee job satisfaction at the BPJS Ketenagakerjaan Regional Office of West Sumatra